Digital scholarship from the bottom up: the library's role in open access student journals - Hall, Robyn (My University, 2013)
Open Journal Systems (OJS) is open source publishing software that has been adopted by scholarly communities around the world. Typically, it is hosted by academic libraries and used by faculty and graduate students to disseminate research articles independent of proprietary, for-profit journal publishers. Increasingly, however, educators are using this software for assignments and initiatives that give undergraduate students hands on experience with open access publishing of their own digital works and that of their peers. Drawing on a range of examples, this session will highlight ways that librarians can provide technical support, editorial guidance, and media/digital literacy instruction to help create and maintain open access student journals. Participants will also have an opportunity to see the inner workings of OJS while being asked to consider the possibilities and implications of managing an open journal hosting service at their own library, be it public, academic, or special.
Presented at Netspeed 2013 in Calgary, Alberta on October 24, 2013.
Keywords: open access; library publishing; Open Journal Systems; undergraduate students